2020
DOI: 10.1177/0033688220917221
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service EFL Teachers’ Conceptions of Learning about SLA through online Discussion Forums and WhatsApp in Blended Learning

Abstract: Online discussion forums are a popular learning tool commonly used in blended learning. Despite the widespread use of this tool, pre-service English as a Foreign Language (EFL) teachers’ conceptions of learning disciplinary concepts through online-discussion forums are under researched. This study aims at filling this gap by describing the conceptions of learning through such forums held by a group of 16 Mexican, pre-service EFL teachers enrolled in an undergraduate Second Language Acquisition course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…In Rambe andMkono (2019), andCetinkaya (2017), participants reported that students felt much relaxed to continuously ask questions in minimal formal WhatsApp settings compared to other means. The current study further agrees with the earlier studies which revealed that WhatsApp messaging was effective in mediating teaching, learning and supervision of graduate students (Fadda et al, 2020;Oyewole et al, 2020;Sandoval-Cruz et al, 2020;Cetinkaya, 2017).…”
Section: Online/virtual Research Supervisionsupporting
confidence: 92%
“…In Rambe andMkono (2019), andCetinkaya (2017), participants reported that students felt much relaxed to continuously ask questions in minimal formal WhatsApp settings compared to other means. The current study further agrees with the earlier studies which revealed that WhatsApp messaging was effective in mediating teaching, learning and supervision of graduate students (Fadda et al, 2020;Oyewole et al, 2020;Sandoval-Cruz et al, 2020;Cetinkaya, 2017).…”
Section: Online/virtual Research Supervisionsupporting
confidence: 92%
“…This article addresses these needs by presenting the results of a phenomenographic study carried out with African in-service computer science teachers with varying teaching experiences. The phenomenography approach has been utilized in previous studies, for example, to understand teachers' conception of mobile learning [1], e-learning studies [16], online teaching [17], cloud-based applications [18] and ICT integration [19] among others. The phenomenography research approach is applied in this study to obtain insights from the teachers' assumptions of machine learning and find variations in their opinions.…”
Section: Trends and Gaps In Teaching Machine Learning Researchmentioning
confidence: 99%
“…shows that preservice EFL teacher students use WhatsApp to communicate and discuss with each other (Sandoval-Cruz et al, 2020) since they are reluctant to express disagreements during online discussion forum available on Moodle LMS as their online learning platform. Their reluctance and preference of using WhatsApp as online discussion forum can be for the reason of their cultural politeness norms.…”
Section: Another Research Conducted In Mexican Blended Learning Envir...mentioning
confidence: 99%